Validation and proposal for cut-off values of an abbreviated version of the Alcohol Use Disorder Identification Test using the Korean National Health and Nutrition Examination Survey - Jae Hee Lee; Kyoung Ae Kong; Duk Hee Lee; Yoon Hee Choi; Koo Young Jung (Clinical and Experimental Emergency Medicine, 2018)
Objective Several abbreviated versions of the Alcohol Use Disorder Identification Test (AUDIT) have been developed and are widely used in clinical settings. In this study, we provide evidence supporting the use of abbreviated versions of AUDIT by comparing the utility of various abbreviated versions and determining cut-off values for the population of South Korea. Methods Data were obtained from the 4th to 6th Korean National Health and Nutrition Examination Surveys. After calculating the whole AUDIT score, we applied the cut-off value of at-risk drinking proposed by the World Health Organization and divided the study sample into normal and at-risk drinking groups. Receiver operating characteristic curves were drawn for AUDIT-3rd question (Q3) alone, AUDIT-quantity and frequency (QF), AUDIT-consumption (C), AUDIT-4, and AUDIT-primary clinic (PC), and optimal cut-off values were obtained for each group. Results A total of 46,450 subjects were analyzed. The at-risk drinking group comprised 29.2% of all subjects. The area under receiver operating characteristic curve (AUROC) of the abbreviated versions of AUDIT increased from 0.954 to 0.991 as the number of questions increased from one to four. The differences in AUROC between the abbreviated versions of AUDIT were statistically significant. The most appropriate cut-off values for AUDIT-Q3 alone, AUDIT-QF, AUDIT-C, AUDIT-4, and AUDIT-PC for adults over age 19 were 2, 4, 5, 6, and 4 points, respectively. Conclusion As the number of items analyzed increased from one to four items, the AUROC increased to a statistically significant level. Cut-off values for abbreviated versions of AUDIT are similar in South Korea to other countries.